Embodied climate impacts in urban development: a neighbourhood case study - Simon Sjökvist; Nicolas Francart; Maria Balouktsi; Harpa Birgisdottir (Buildings & Cities)
The urgent need to reduce greenhouse gas emissions and the increasing share of embodied carbon in life-cycle impacts underscore the necessity of mitigating construction and demolition impacts to align with the Paris Agreement. Urban planning significantly influences material flows, with a substantial portion of construction occurring in planned urban development areas (UDAs), such as 76% in Copenhagen, Denmark. However, research on UDAs is limited, with most life-cycle assessments (LCAs) focusing on individual buildings. This study examines the embodied CO2e emissions from buildings and infrastructure in a newly developed UDA, using an archetype-based LCA approach that combines both on-site and average data, which can serve as a stepping stone for a more comprehensive analysis. The study shows that most emissions in the studied UDA occur upfront and are attributed to new building construction. The studied UDA featured several refurbished buildings, repurposed into housing and offices, but their reuse only made a small difference when considering embodied emissions for the entire UDA. Other UDAs may exhibit a different emission profile. Lastly, the study compares neighbourhood and city-scale impacts to absolute environmental boundaries, highlighting the significant climate impacts of urban planning, particularly in UDAs. Policy relevance Urban planning has a significant influence on climate impacts. The substantial amounts of embodied CO2e attributed to planned UDAs, particularly emissions occurring upfront and relative to absolute environmental boundaries, suggest the need to rethink current urban planning frameworks to better align with absolute environmental boundaries and the goals of the Paris Agreement. The results offer insights for developing contextual mitigation measures; the large share of CO2e emitted by new buildings underscores the potential of low-carbon technologies and materials and the broader impact of regulatory targets. Moreover, the limited relative impact of reuse in the studied UDA suggests the need for planning models that prioritise existing building inventories over new construction. Ultimately, the findings may also suggest the need to reconsider the overall scale of permissible building rights altogether.